The Success of Project-Based Learning Model with the Aid of Technology - Reza Amelia Fitri; Eka Setiana; Indah Nurcahya Pribadi; Adi Fitra Andikos (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to analyze the success of implementing the project-based learning model (Project-Based Learning) with the help of technology in improving student learning outcomes. The research uses a qualitative approach with a descriptive design. Data was collected through observation, in-depth interviews, and documentation on class X students in SMKN 1 Sungai Rumbai . Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results show that the application of a project-based learning model with the help of technology has a positive impact on student engagement, mastery of material, as well as critical thinking and collaboration skills. Key success factors include the availability of technological devices, teacher support in facilitating learning, and the relevance of the project to the student's life context. However, obstacles were found such as a lack of student digital literacy and limited access to technology in several areas. This research concludes that the project-based learning model with the help of technology can be an effective strategy for improving the quality of learning if supported by adequate resources. Recommendations are given to improve teacher training regarding educational technology and expand access to digital infrastructure in schools.